Is there a link between X-efficiencies and the performance of listed banks in China? - Zhang, Chuchu (2016)
This paper explores the determinants of performance in Chinese banking sector, particularly the effect of cost X-efficiency, for forty-one listed banks over the period 2009-2014. The Stochastic Frontier Approach (SFA) is employed to estimate the X-efficiency while the Generalized Method of Moments (GMM) is used to assess determinants of bank performance in China. The results show the cost X-efficiency has downward trend with the average value of 0.513, which can be affected positively by higher cost of borrowed funds, more gross loans, more off balance sheet items, and more other earning assets. It is significantly and positively related to the bank profitability. Apart from this, higher profitability is also associated with the higher capital adequacy and lower credit risk inside the bank, and higher GDP growth rate, higher unemployment rate and lower inflation rate in the macroeconomic environment.